ANALYSIS OF GOVERNMENT INTERNAL CONTROL SYSTEM ON PROCUREMENT OF HEALTH GOODS DURING THE COVID-19 PANDEMIC AT THE HEALTH OFFICE OF NORTH SUMATERA PROVINCE - Sungkunen Purba; Dadang Suwanda; Basuki Rachmat; Eljawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The COVID-19 pandemic in 2020 has had an impact on the health of the Indonesian people. The spread of the COVID-19 pandemic is increasing day by day and attacking the health of the Indonesian people, causing more casualties and material losses and affecting social, economic, and community welfare aspects. The central government has also issued many policies to deal with the handling of the COVID-19 pandemic, one of which is the procurement mechanism for goods in the context of the COVID-19 pandemic. The Financial and Development Supervisory Agency asked the Regional Government to pay attention to the procurement of health materials and medical devices. Procurement of Goods is a critical area for misappropriation of state funds so that it can cause the Indonesian Government's hopes for handling the COVID-19 pandemic to fail. Through refocusing activities, the total budget of the North Sumatra Provincial Government for handling the COVID-19 pandemic is 1.5 trillion with a 3-stage process. For this reason, a Government Internal Control System is needed in the Procurement of Goods, especially in the Health sector, in the hope of preventing misappropriation of state funds in the Procurement of Goods. This study uses a mix method that combines quantitative descriptive followed by qualitative methods with an inductive approach and is completed with data triangulation. The sample in this study was the Expenditure Treasurer and the Goods and Services Procurement Unit at the North Sumatra Provincial Health Office. The data collection instrument was a questionnaire with a grand theory, namely the Government Internal Control System using the Likert Scale and Interview measurement scale. Furthermore, data analysis was carried out through data reduction by understanding and analyzing the existing data, then presenting the data and finally drawing conclusions and recommendations. Based on the results of the study, respondents gave an average SPIP score of 4.26 (Government Internal Control System) with the results of the analysis showing that it had been carried out according to theory and legalistic Government Internal Control System. However, there are still shortcomings, namely certified human resources for procurement of goods and services so that control over procurement activities is in accordance with the budget for handling the COVID-19 pandemic and the need for significant action on information technology. This is done to answer the challenge of clean Procurement of Goods from misappropriation of state funds